Analisis Struktur Biaya Usaha Tani Baby Buncis di Kecamatan Lembang Kabupaten Bandung Barat - Subandi, Yadi Nugraha; Suminartika, Eti; Sulistyowati, Lies (Universitas Galuh, 2024)
This research aims to analyze the cost structure of baby bean farming in Lembang District. This research was carried out by sampling using Cluster Random Sampling, so a sample size of 96 people was obtained from a total population of 2,349 baby bean farmers. The data was analyzed using the Revenue Cost Ration to analyze income. The results of the research show that the types of costs for baby bean farming show that the largest percentage of baby bean farming costs is labor costs with a value of Rp. 16,200,000 (35.34%). The high percentage of costs for this work requirement is due to the large number of workers needed in farming activities from land processing to harvest. The total costs for baby bean farming are IDR 45,834,601 per season per hectare with revenues of IDR 88,380,000. This means that the baby bean business is worth cultivating but its productivity must be further increased. Based on calculations, the baby bean farming income per hectare per season is IDR 42,545,399,- with an RC ratio of 1.93. An RC value > 1 indicates that the baby bean business carried out by farmers is profitable.